Impact of Transcranial Direct Current Stimulation and Cognitive Training on Frontal Lobe Neurotransmitter Concentrations - Alvarez-Alvarado, Stacey; Boutzoukas, Emanuel M.; Kraft, Jessica N.; O’Shea, Andrew; Indahlastari, Aprinda; Albizu, Alejandro; Nissim, Nicole R.; Evangelista, Nicole D.; Cohen, Ronald; Porges, Eric C.; Woods, Adam J. (Frontiers in Aging Neuroscience, 2021)
Objective: This study examines the impact of transcranial direct current stimulation (tDCS) combined with cognitive training on neurotransmitter concentrations in the prefrontal cortex. Materials and Methods: Twenty-three older adults were randomized to either active-tDCS or sham-tDCS in combination with cognitive training for 2 weeks. Active-tDCS was delivered over F3 (cathode) and F4 (anode) electrode placements for 20 minutes at 2 mA intensity. For each training session, 40-minutes of computerized cognitive training were applied with active or sham stimulation delivered during the first 20-minutes. Glutamine/glutamate (Glx) and gamma-aminobutyric acid (GABA) concentrations via proton magnetic resonance spectroscopy were evaluated at baseline and at the end of 2-week intervention. Results: Glx concentrations increased from pre to post-intervention (p = .010) in the active versus sham group after controlling for age, number of intervention days, MoCA scores, and baseline Glx concentration. No difference in GABA concentration was detected between active and sham groups (p = .650) after 2-week intervention. Conclusions: Results provide preliminary evidence suggesting that combining cognitive training and tDCS over the prefrontal cortex elicits sustained increase in excitatory neurotransmitter concentrations. Findings support the combination of tDCS and cognitive training as a potential method for altering neurotransmitter concentrations in the frontal cortices, which may have implications for neuroplasticity in the aging brain.